Construction of Legal Norm on Reporting of Multiple Positions for Foreign Workers - Atika Saraswati; M. Alvi Syahrin (Jurnal Ilmiah Kajian Keimigrasian, 2020)
Year 2020 is the beginning of years for The Directorate General of Immigration to start its strategic planning for the next 5 (five) years compiled as document of Directorate General of Strategic Plan of 2020-2024. The Directorate General's Strategic Plan comply The Ministry of Justice and Human Rights Strategic Plan which sets to document of RPJMN-IV determined in accordance to the Vision and Mission of the Elected President. Reflected by the Vision, Mission and also the Government's Strategic/ National Priorities for the next 5 (five) years, President Jokowi hoped for development acceleration especially in aspects of human resource and regional development. Some methods are by inviting as much investment as possible and implementing bureaucratic reforms in governance. Sinergyzing with the Vision of the President, the Directorate General of Immigration formulated the direction with a change in its focus. Formerly, in year 2015-2015, focus of immigration policies are to strengthen immigration public service and law enforcement while for the next 5 years the focus is aimed to be slightly change to the effort to strengthen state security and facilitate public welfare development. Therefore this paper will describe efforts planned to be taken to strengthen immigration function as facilitator of public welfare development. Based on the description as mentioned before, the Research Question for this paper is : “How will the function of immigration as the facilitator of public welfare development will be directed in the strategic planning of the Directorate General of Immigration for 2020-2024?". The aim is to study and analyze immigration policy and its strategic objectives. This study uses descriptive qualitative method with the using of primary and secondary data gathered by the author.